Substrates for surface-enhanced Raman spectroscopy based on TiN plasmonic antennas and waveguide platforms - Jun Chen (Results in Physics, 2020)
As a non-invasive detection technology, integrated sensors for surface-enhanced Raman spectroscopy (SERS) have been widely studied to realize inexpensive in situ measurements. Unfortunately, most existing SERS sensors are comprised of noble metals nano-structure, which introduce the disadvantages of high cost, poor adhesion, and high wear rates. In this study, integrated SERS substrates based on TiN plasmonic antennas and Si waveguides are investigated. The electromagnetic coupling between TiN plasmons and Si waveguides are demonstrated. In addition, we analyze Raman enhancement as a function of the geometric parameters of the antenna and find a maximum enhancement factor of 9.7 × 105. These SERS substrates provide not only strong enhancement but also low cost and mechanical stability due to the all-dielectric structure. The results show that the proposed configuration leads to inexpensive integrated SERS sensors that can be used for on-road drug detection, environmental protection, and other applications.